Systematic Review and Meta-Analysis of Renin–Angiotensin–Aldosterone System Blocker Effects on the Development of Cardiovascular Disease in Patients With Chronic Kidney Disease - Yanai, Katsunori; Ishibashi, Kenichi; Morishita, Yoshiyuki (Frontiers in Pharmacology, 2021)
Background: Cardiovascular events are one of the most serious complications that increase the risk of mortality and morbidity in pre-dialysis and on-dialysis chronic kidney disease (CKD) patients. Activation of the renin–angiotensin–aldosterone system (RAAS) is considered to contribute to the development of cardiovascular events in these populations. Therefore, several kinds of RAAS blockers have been frequently prescribed to prevent cardiovascular events in patients with CKD; however, their effectiveness remains controversial. This systematic review focuses on whether RAAS blockers prevent cardiovascular events in patients with CKD. Method: PubMed was searched to retrieve reference lists of eligible trials and related reviews. Randomized prospective controlled trials that investigated the effects on cardiovascular events in CKD patients that were published in English from 2010 to 2020 were included. Results: Among 167 identified studies, 11 eligible studies (n = 8,322 subjects) were included in the meta-analysis. The meta-analysis showed that RAAS blockers significantly reduced cardiovascular events in on-dialysis patients with CKD (three studies; odds ratio [OR], 0.52; 95% confidence interval [CI], 0.36 to 0.74; p = 0.0003), but there was no significant difference in pre-dialysis patients with CKD because of the heterogeneity in each study (eight studies). We also investigated the effects of each kind of RAAS blocker on cardiovascular events in CKD patients. Among the RAAS blockers, mineralocorticoid receptor antagonists significantly decreased cardiovascular events in pre-dialysis or on-dialysis patients with CKD (four studies; OR, 0.60; 95%CI, 0.50 to 0.73, p < 0.0001). However, angiotensin receptor blockers did not show significant effects (four studies; OR, 0.65; 95%CI, 0.42 to 1.01; p = 0.0529). The effects of angiotensin converting enzyme inhibitors and direct renin inhibitors on cardiovascular events in patients with CKD could not be analyzed because there were too few studies. Conclusion: Mineralocorticoid receptor antagonists may decrease cardiovascular events in pre-dialysis or on-dialysis patients with CKD.